Perceptions on the adoption or use of waste to energy (WtE) technologies among waste managers in Gauteng - Mokgolobotho, Ingrid Konkong (University of the Witwatersrand, Johannesburg, 2024)
The Gauteng Province, increase in population growth, urbanisation, industrialisation and economic activity has resulted in increased amounts of generated municipal solid waste (MSW). There are concerns about landfill airspace depletion, energy poverty, environmental concerns that create greenhouse gases, air pollution and water contamination. The province also requires electricity to keep its economic activity functional, while providing its citizens with electricity. The research is a qualitative study, with the purpose of understanding how waste managers in the waste industry perceive the adoption or use of waste to energy (WtE) technologies in Gauteng. Semi-qualitative interviews were held, face-to-face and on Microsoft Teams. The sample chosen were waste managers who were knowledgeable on the research topic. Thematic analysis was used to analyse the data from the semi-qualitative interviews. Data triangulation was used to establish the credibility/validity of the interview findings. The findings in the study from the semi-qualitative interviews and literature review were aligned with regards to the role waste managers’ play in procuring waste to energy technologies as well as the benefits on the uptake of WtE technologies, which are improved waste management practices, less environmental challenges and the introduction of new revenue streams. Waste managers are also viewed as researchers, collaborators and educators. The study found that some of the factors that influence the perceived ease of use as well as perceived usefulness of WtE technologies include the feasibility and affordability of these technologies, access to finance, the availability of technical, training and skills transfer, potential employment opportunities and the need to diversify the energy supply iii The challenges observed by the participants were the lack of stakeholder engagement and sufficient education, lack of adequate legislature and poor governance as well as lack of access to capital. The enablers were noted as equipment tax returns, introduce landfill tax, high landfill entry gates, energy sales, carbon credits as well as educating and involving all waste generators and recyclers. To attract investors, participants noted that there should be transparency and simplified contracts, having relevant collaborations, the need for grants and assurance on return on investment
A research report submitted in fulfillment of the requirements for the Master of Management in Energy Leadership, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Waste Managers; Waste to Energy technologie; Acceptance Model; SDG-9: Industry, innovation and infrastructure; SDG-7: Affordable and clean energy